Shifting social imaginaries in the Hellenistic period : narrations, practices, and images - Stavrianopoulou, Eftychia, 1962- (Mnemosyne, Supplements, 2013)
There is a long tradition in classical scholarship of reducing the Hellenistic period to the spreading of Greek language and culture far beyond the borders of the Mediterranean. More than anything else this perception has hindered an appreciation of the manifold consequences triggered by the creation of new spaces of connectivity linking different cultures and societies in parts of Europe, Asia and Africa. In adopting a new approach this volume explores the effects of the continuous adaptations of ideas and practices to new contexts of meaning on the social imaginaries of the parties participating in these intercultural encounters. The essays show that the seemingly static end-products of the interaction between Greek and non-Greek groups, such as texts, images, and objects, were embedded in long-term discourses, and thus subject to continuously shifting processes.